Investigation into the Production of Melanin from By-Products of Huangjiu Brewing - Congyu Lin; Peiqi Lu; Jingqiu Ma; Tao Kan; Xiao Han; Shuangping Liu; Zhongwei Ji; Jian Mao (Foods)
Melanin is a high value bioproduct generated through the fermentation of Aureobasidium pullulans, playing a crucial role in various fields, including food, medicine, environmental protection, and materials science. However, its high production costs and low synthetic yields significantly limit its applications. Therefore, it is essential to identify high-yield strains, reduce production costs, and optimize fermentation strategies. In this study, a high melanin-yielding Aureobasidium pullulans 53LC7 was screened and identified, and the fermentation process was optimized based on melanin yield, color value, and pullulan yield. The results indicated that the melanin yield peaked at an initial pH of 6.0, temperature of 27 °C, fermentation time of 6.5 d, and inoculation quantity of 2.5%, achieving a melanin yield of 16.33 g/L. Subsequently, huangjiu lees, a byproduct of huangjiu production, was incorporated into the fermentation medium, resulting in a melanin yield of 5.91 g/L. This suggests that the Aureobasidium pullulans was not effectively utilizing huangjiu lees. To address this, we employed an adaptive evolution strategy, which increased the melanin yield to 8.72 g/L. The enhanced production was correlated with the expression of key genes, including FKS, PKS, and Cmr1. Finally, cellulase was utilized to convert the crude fibers in huangjiu lees, which were difficult to utilize, into usable substrates, while pullulanase was employed to minimize byproduct formation in the fermentation system, resulting in a melanin yield of 19.07 g/L. This study not only provides promising strains for further research but also offers valuable insights for resource production technologies.